Pengaruh Penerapan Modifikasi Permainan Roblox Mosar Terhadap Perkembangan Motorik Kasar Anak - Elva, Elva Novianti Putri; Neng Awalia Farida; Dede Ridwan (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
The development of gross motor skill is very important to stimulate and to attention. This is because gross motor development influences physiological, social and cognitive development. Children's habit of moving or having good gross motor skills tends to improve. Increasing self-confidence also makes it easier for children to socialize. Meanwhile, children who experience gross motor development problems often feel embarrassed and close themselves off from their peers. Apart from that, the prevalence of excessive screen time is also the biggest factor that makes children tend to be passive, and of course their gross motor activities become less developed. Therefore, gross motor development cannot be considered trivial. This research aims to determine whether or not there is an influence from implementing the Roblox Mosar game on the gross motor development of children aged 5-6 years at Dewi Sartika 1 Kindergarten Gegerbitung Kab. Sukabumi. Based on this, this research is a type of experimental research using a quantitative approach. The design used is One-Group Pretest-Posttest Design. Sampling is a saturated sample where less than 30 people are sampled, therefore all samples receive treatment, using a treatment test of 10 activities from 5 indicators. The results of this research conclude that there is an influence from implementing the Roblox Mosar game on the gross motor development of children aged 5-6 years at Dewi Sartika 1 Kindergarten Gegerbitung District. Sukabumi. It is proven from the results of data analysis using Paired-Samples t-Test that the Sign value is 0.01 < 0.05. That means Ha is accepted and H0 is rejected.